(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available. Key words: Acacia auriculiformis; micropropagation; direct organogenesis; shoot tips; nodal segment explants Bangladesh j. genet. biotechnol. 6 (1&2): 33-35, 2005 (June & December)